Strategies Used in Feigning Hearing Loss - Martin, Frederick N.; Champlin, Craig A.; McCreery, Tiana M. (Journal of the American Academy of Audiology, 2001)
Thirty unsophisticated participants with normal hearing were paid to simulate a hearing loss according to their success in "deceiving" the examiner. The behaviors that these "malingerers" manifested are described . A post-examination interview revealed the strategies used by these participants, which may reflect those strategies used by patients who truly attempt to feign a hearing loss .Abbreviations : AC = air conduction, BC = bone conduction, NOHL = nonorganic hearing loss, PB = phonetically balanced, PTA = pure-tone average, SRT = speech recognition threshold, WRS = word recognition score
Keywords: Malingering; nonorganic hearing loss; nonorganicity